Recent advancement of energy internet for emerging energy management technologies: Key features, potential applications, methods and open issues - Hannan M.A.; Ker P.J.; Mansor M.; Lipu M.H.; Al-Shetwi A.Q.; Alghamdi S.M.; Begum R.A.; Tiong S.K. (Elsevier Ltd, 2024)
This article deals with a thorough investigation of the energy internet towards future emerging technologies for energy distribution and management to solve existing limitations and enhance the performance of future sustainable energy. In consequence, a comprehensive review of energy internet features, applications, methods and existing issues and challenges are explained by developing arguments for future prospects. Key features of the energy internet such as energy sources, communication technologies, data computation, energy management systems and financial analysis are highlighted to enhance the energy efficiency, reliability, and security of the power network. Different energy internet application architectures and models are demonstrated for regulatory bodies under different dimensional concepts, networks, and layers. This article also explains the energy internet methods related to different programming approaches, artificial intelligence, and optimization algorithms for achieving granted reliability and enabling a decentralized energy market with a two-way energy flow. Furthermore, the present review focuses on the various issues and challenges of existing energy internet platforms related to safety, security, standards, protocols, costing and complexity as well as provides recommendations for future energy internet toward efficient energy distribution and management. Moreover, the study analyzes the impact of the energy internet on the conventional power grid and provides a global landscape of energy internet projects to make it more effective, dependable, and sustainable. All the highlighted insights of this review collectively inspire advancements in the energy internet platform for future energy data dissemination and management. 2023 The Authors